The impact of valproic acid administration: Effects on the growth of tongue cancer cells - Rasiani, Salma (Asian Journal of Toxicology, Environmental, and Occupational Health, 2024)
Background: Tongue cancer represents the predominant malignancy within the oral cavity (25 – 40% of squamous cell carcinoma), necessitating treatment modalities such as surgery, radiotherapy, and chemotherapy. Valproic acid, an antiepileptic medication, functions as a histone deacetylase inhibitor or activator of anti-tumor signaling pathways. Objective: To deepen our understanding of the effects of valproic acid on the viability, cytotoxicity, proliferation, and migration capabilities of HSC-3 cells. Method: This study employed an in vitro laboratory approach, exposing HSC-3 cells to valproic acid. The experimental groups included a negative control with culture media devoid of valproic acid, and treatment groups exposed to valproic acid at concentrations of 145 ppm, 180 ppm, and 355 ppm, respectively. Results: Significant differences (p-value < 0.05) were observed between HSC-3 cells treated with valproic acid (145 ppm, 180 ppm, and 355 ppm) and the control group in terms of viability, cytotoxicity, proliferation, and migration. Reduced cell viability, increased cytotoxicity, and decreased proliferation were noted. Migration assays indicated suppressed migration of HSC-3 cells.  Conclusion: In summary, this study reveals that valproic acid exerts substantial effects on various aspects of HSC-3 cell behavior. It decreases cell viability, enhances cytotoxicity, suppresses proliferation, and inhibits cell migration. These findings highlight the potential of valproic acid as a therapeutic agent for tongue cancer by targeting crucial cellular processes involved in cancer progression. Further research and clinical trials are essential to confirm these effects and explore their application in cancer treatment strategies. Novelty/Originality of this article:: This study shows valproic acid has potential as a therapeutic agent for tongue cancer by decreasing cell viability, increasing cytotoxicity, suppressing proliferation, and inhibiting migration of HSC-3 cells. These findings introduce a new application of valproic acid as an anticancer agent, expanding the use of antiepileptic drugs. This study opens up opportunities for developing more effective tongue cancer therapies and encourages further research and clinical trials to validate these findings.